Fasting glucose mediates the influence of genetic variants of SOD2 gene on lean non-alcoholic fatty liver disease - Wu, Na; Zhai, Xiangyu; Yuan, Fan; Li, Jie; Yu, Ning; Zhang, Fengwei; Li, Dong; Wang, Jianying; Zhang, Lei; Shi, Yi; Ji, Guang; He, Guang; et al. (Frontiers in Genetics, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) imposes an enormous burden on public health, and a large proportion of NAFLD patients are lean with normal body weight, which is rarely mentioned. We conducted this study to determine the mediation effects of fasting glucose on the relationships between genetic variants of SOD2 and the susceptibility of lean NAFLD in the elderly Chinese Han population. Methods: Data in this manuscript were collected in a cross-sectional study among 5,387 residents (aged ≥60 years) in the Zhangjiang community center, Shanghai, China, in 2017. Ten (single nucleotide polymorphisms) SNPs previously reported to be related to NAFLD and obesity, including rs9939609, rs1421085, rs9930506, rs626283, rs641738, rs4880, rs58542926, rs738409, rs2281135, and rs2294918 were genotyped. The associations between genetic variations in SOD2 and fasting glucose in five genetic models were analyzed with the SNPassoc R package and rechecked with regression analysis. Mediation models were conducted to explore whether fasting glucose can mediate the association between SNPs and the susceptibility of lean NAFLD. Results: In this study, lean NAFLD individuals had a higher waist circumference and waist-to-hip ratio, ALT, and fasting glucose than lean non-NAFLD individuals (p < 0.050). In comparison, the AA genotypic frequency of rs4880 in SOD2 gene was much lower in lean NAFLD patients (p = 0.005). And rs4800 had a significant indirect effect on lean NAFLD incidence mediated by fasting glucose (p < 0.001). Conclusion: For the first time, the mediation effect of fasting glucose on the association of rs4880 in SOD2 with the susceptibility of lean NAFLD was clarified in the elderly Chinese Han population. It emphasized the connection between glucose homeostasis and oxidative stress in the mechanisms of lean NAFLD.